Addition of Basal Insulin to Oral Antidiabetic Agents in Patients with Inadequately Controlled Type 2 Diabetes Leads to Improved HbA1c Levels: Metabolic Control, Frequency of Hypoglycemia, and Insulin Titration Analysis as Results of a Prospective Observational Study (BALI Study) - Brož, Jan; Janíčková Ždárská, Denisa; Štěpánová, Radka; Kvapil, Milan (Diabetes therapy, 2019)
INTRODUCTION: Despite the continuously growing number of therapeutic options for patients with type 2 diabetes mellitus (T2DM), a large percentage of these individuals fail to achieve their glycated hemoglobin (HbA1c) target. The aim of this study was to determine the change in metabolic control in insulin-naïve T2DM patients inadequately controlled with oral antidiabetic drugs (OADs) at 6 months after initiating basal insulin treatment as add-on to existing OADs. METHODS: This was a non-interventional prospective study conducted from June 2013 to December 2014 in 137 centers in the Czech Republic under routine clinical practice conditions. Adult patients whose diabetes was uncontrolled on their current OAD treatment (HbA1c ≥ 53 mmol/mol; Diabetes Control and Complications Trial [DCCT]-HbA1c 7%) and whose physician had decided to initiate treatment on a basal insulin regimen were documented over a 6-month period beginning from the time of initiation of basal insulin treatment. RESULTS: Overall, 1426 T2DM patients were included in the study, of whom 53% were male. The mean age of the study population was 63.8 ± 10.1 years, mean body mass index was 31.5 ± 5.3 kg/m2, and mean duration of diabetes was 10.2 ± 5.3 years. At the 6-month follow-up, the target HbA1c level of 53 mmol/mol (DCCT < 7%) was achieved by 18% of patients. The mean HbA1c overall had decreased from 77.2 ± 15.1 mmol/mol (DCCT 9.21 ± 1.38%) at baseline to 63.2 ± 12.5 mmol/mol (DCCT 7.93 ± 1.14 %) at the 6-month follow-up. This difference was significant at p < 0.001. The largest mean reduction in HbA1c, i.e., 20.9 mmol/mol (DCCT 2.4 %) was observed in the group of patients with a baseline HbA1c of ≥ 9%. The mean daily basal insulin dose at 6 months was 18.8 ± 8.9 units. Symptomatic hypoglycemia was reported in 12.3% of patients, of those only one patient (0.1%) suffered from severe hypoglycemia. CONCLUSION: The addition of basal insulin to the therapeutic regimen of insulin-naïve T2DM on OAD treatment resulted in an improved metabolic control of diabetes after 6 months of treatment. However, most patients did not achieve their HbA1c target, probably also due to inadequate titration of basal insulin. FUNDING: Sanofi, Czech Republic.
Keywords: Hypoglycemia; Insulin initiation; Type 2 diabetes; HbA1c; Titration; Basal insulin